Precision rehabilitation for aphasia by patient age, sex, aphasia severity, and time since stroke? A prespecified, systematic review-based, individual participant data, network, subgroup meta-analysis - Brady, Marian C.; Ali, Myzoon; VandenBerg, Kathryn; Williams, Linda J.; Williams, Louise R.; Abo, Masahiro; Becker, Frank; Bowen, Audrey; Brandenburg, Caitlin; Breitenstein, Caterina; Bruehl, Stefanie; Copland, David A.; et al. (My University, 2022)
Stroke rehabilitation interventions are routinely personalized to address individuals' needs, goals, and challenges based on evidence from aggregated randomized controlled trials (RCT) data and meta-syntheses. Individual participant data (IPD) meta-analyses may better inform the development of precision rehabilitation approaches, quantifying treatment responses while adjusting for confounders and reducing ecological bias.
Keywords: Stroke; aphasia; individual participant data; network meta-analysis; rehabilitation; speech and language therapy